(untitled) (Jurnal Orthopaedagogia, 2025)
ABSTRACT Deaf children are children who have below-average intelligence that impacts on academics and difficulties in carrying out activities. Students with disabilities need appropriate media and methods to recognise numbers. Therefore, the number wheel learning media can be an alternative in overcoming these problems. This study aims to determine the effect of the number pinwheel learning media on improving the ability to recognise numbers of grade IV students in SLB Bhina Putera Surakarta in the 2024/2025 school year. This research is a quantitative study with a pre-experimental one-group pretest-posttest design. The sampling technique used was a saturated sample with a total of 6 students. The instrument used was a written test. Validity was tested using content validity with Aiken’s V formula and reliability test using internal consistency with KR-20 formula. This study used descriptive and inferential data analysis techniques with the SPSS version 25 application. The average pretest score, which was 35, increased to 83.33 on the posttest. Inferential data analysis using non-parametric methods with the Wilcoxon Signed Rank Test, resulting in a Z value of -2.214 and Asymp. Sig (2-tailed) of 0.027 with a significance level of 0.05. The conclusion of this study is that the number wheel learning media is proven to have a significant effect on improving the ability to recognise numbers in students.